Structure and Functions of the Liver (HEPAR) - Utkurxodjayevna, Kattaxodjayeva Dinara; Xushbakovich, Samatov Akmal; Gulom qizi, Samatova Maftuna (American Journal of Bioscience and Clinical Integrity, 2026)
This paper examines the growing liver anlage , which is divided into two parts – cranial and caudal. The liver is the second-largest organ in the human body (the largest being the skin) and the largest gland, weighing approximately 1-1.5 kg. It also serves as a link between the digestive system and the bloodstream. Most of its blood (70-80%) comes from the portal vein, which collects blood from the stomach, intestine, and spleen; only a smaller volume (20-30%) comes from the hepatic artery.